Assistance in improving the quality of financial management of the oyster mushroom business for the disable persons at DPO Restu Abadi Purworejo - Hesti Respatiningsih; Nur Siyami; Rizki Dewantara; Dewi Chirzah; Arkan Salsabila Asegaf; Hilda Nova Indira (Universitas Muhammadiyah Magelang, 2023)
This community service activity is undertaken to enhance the quality of financial management, aiming to attain financial independence for members of business groups with disabilities. The approach involves training and mentoring, engaging both academics and practitioners specializing in financial literacy and inclusion. The success of this service program is evident in the increased knowledge and skills of the partners, encompassing the preparation of plans, business financial reports, financial literacy, and inclusion. Additionally, there has been an improvement in partners' access to financial institutions. The challenges of partner indiscipline in recording finances and pricing strategy problems can be effectively addressed through the use of the SIMAKE application. This application facilitates easy recording of transactions and determination of product prices.